A New Enzyme-Free Electrochemical Immunoassay for Escherichia coli Detection using Magnetic Nanoparticles. (22nd January 2016) - Kozitsina, A.; Svalova, T.; Malysheva, N.; Glazyrina, Y.; Matern, A.
ABSTRACT: This paper reports a novel enzyme-free electrochemical immunoassay for Escherichia coli (ATCC 25922) that involves the formation of an immunocomplex between antibodies immobilized on the surface of a platinum electrode and bacteria-labelled magnetite nanoparticles. Magnetite nanoparticles modified with chitosan were used as the signal label in the immunoassay. The main novelty is the collection of an electrochemical signal from a magnetic nanolabel included within the immunocomplex on the electrode surface. The developed immunosensor is highly specific, enabling the determination of E. coli from 10 to 10 5 colony-forming units (CFU)/mL with the relative standard deviation below 10%. The limit of detection for the immunosensor was 9.3 CFU/mL. Bacteria were determined in model mixtures and real samples. The recovery was between 95 and 99%, comparable with results from enzyme-linked immunosorbent assays.